Capsular contraction following immediate reconstructive surgery for breast cancer – An association with methylene blue dye - Singh-Ranger, Gurpreet (BioMed Central, 2004)
Capsular contraction following implantation of breast prostheses occurs in 2–33% of patients undergoing breast augmentation. This condition can be debilitating for patients, and often requires revisional surgery. The aetiology of capsular contraction is unclear, but may be due to infection, haematoma or foreign body-type reactions. Methylene blue dye is a substance known to cause localised tissue inflammation, and is often used during breast cancer surgery to allow identification of the sentinel lymph node. We report a case of Baker Grade 4 capsular contraction necessitating revisional surgery, occurring in a patient who underwent immediate breast reconstruction during surgery for breast cancer. Methylene blue dye was used to locate the sentinel nodes during the original surgery, and was found to have heavily discoloured the prosthesis at subsequent revisional surgery. Capsular contraction may have been caused in part by a localised tissue reaction initiated by, or involving the dye.